IMPROVING STUDENTS‘ LISTENING ABILITYBY WATCHING ENGLISH FILMS - Humiras Betty Marlina Sihombing (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2018)
This paper discusses one of the ways to improve students‘ listening ability. Listening subject provides students with the materials of oral communication by English native speakers that mostly focuses on language expressions. It needs the learners to have listening practice a lot, inside and outside the classroom. Actually in teaching listening many activities can be done and many media can be used to provide students with listening activities in order to improve their listening abilities. One of the students‘ favorite activities is watching English Films. By watching English Films students are introduced to the real context of language and a wide range of vocabulary. After watching English Films students are assigned to make the English Films report. Since many people like watching English Films, assigning students to watch the English Films and make the report of what they have watched is expected to be more enjoyable. However they need to understand the English Films itself before they make their reports. They may watch the English Films twice or even more than twice to understand it, before they are able to make and present the English Films reports in the class. In these activities, the students have to watch and listen to the words, expressions, and sentences said by the characters. There are many advantages of these activities. By watching English Filmss students can learn the correct pronunciation, useful expressions from native speakers. Beside those activities, the students are also asked to write a synopsis of the English Films, find the meaning of useful expressions, understand the moral lesson of the English Filmss and present their own reports.